AgDatabox-Map-Fast Track: Módulo Computacional para Geração de Mapas Temáticos e Delineamento de Zonas de Manejo Automático - Aikes Junior , Jorge (2022)
Precision agriculture consists of applying inputs in the right quantities at the right time and place to maximize yield. There are two important tasks in this process: the generation of thematic maps (TM) and management zones (MZ). Although the TMs and the MZs delineation are extremely important, they depend on great technical knowledge for their construction, so, their use is difficult, especially by producers who do not have access to specialized teams, due to the need for a specialized multidisciplinary team. Thus, this work presents a module (ADB-MAP-FT) able of delineating MZs and generating TMs automatically, integrated with AgDataBox-Map (ADB-Map) application of AgDataBox web platform (ADB; https://adb. md.utfpr.edu.br/). ADB is a web platform to integrate data, software, procedures, and methodologies for digital agriculture. This dissertation was organized in three documents: Book 1: presents concepts, protocols, software, and several examples of use and understand both TMs and MZs. This book is divided into two main parts: the first one presents TMs, their characteristics, importance, use, definitions for the best choice of color scheme, and several examples. The second one presents MZs and several examples. As ZMs design presents several possibilities, definitions, protocols, economic return, options, and most commonly used software are based on a systematic study of literature, constituted from the association of systematic techniques of literature mapping and snowball. Article 1: the web computational module (ADB-MAP-FT) was developed to automatically create TMs and delineate MZs, implementing protocols defined based on extensive bibliographic research. The module and its features are presented using real data in a case study. Paper 2: It was carried out a comparison between the developed module and the most used software in the literature based on the existing state-of-the-art software. The characteristics and technical abilities of software are compared and validated in a case